2021
DOI: 10.22599/bioj.157
|View full text |Cite
|
Sign up to set email alerts
|

Parental Home Vision Testing of Children During Covid-19 Pandemic

Abstract: Background: The Covid-19 pandemic necessitated social distancing restrictions, which placed limitations on access to ophthalmic care to only those who had an imminent risk of sight loss. All other face-to-face consultations were converted to telephone consultations or were postponed. We investigated whether parents were able to test their child's vision using available home vision testing applications, with an aim to aid decision making during a telephone consultation. Methods: Families with follow-up consulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 9 publications
0
35
1
Order By: Relevance
“…This is an important step given that assessment at home introduces more sources of variability. During the COVID-19 pandemic, the use of apps to assess VA at home was evaluated, but one study had a very low participation rate (only 16% of parents that gave consent to participate provided data) (Painter et al 2021), and another reported a modest correlation with clinical tests (Silverstein et al 2021). Therefore, further evaluation of the Amblyopia Tracker app is underway, with parents testing children at home and then testing repeated on return to the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…This is an important step given that assessment at home introduces more sources of variability. During the COVID-19 pandemic, the use of apps to assess VA at home was evaluated, but one study had a very low participation rate (only 16% of parents that gave consent to participate provided data) (Painter et al 2021), and another reported a modest correlation with clinical tests (Silverstein et al 2021). Therefore, further evaluation of the Amblyopia Tracker app is underway, with parents testing children at home and then testing repeated on return to the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…17 18 In a prospective comparative study of app-based home vision testing in children, most families were able to generate results deemed useful for clinical decision making, but parental engagement was low. 19 Face and eyelid-The presence of vesicles and rashes on the face or eyelids suggest herpes simplex infection or herpes zoster ophthalmicus (if the involvement respects the midline of the face and V1 dermatomal distribution (fig 2)). 20 Presence of Hutchinson's sign (involvement of the tip or lateral aspect of the nose) suggests a higher likelihood of ocular involvement in herpes zoster ophthalmicus.…”
Section: Fig 1 |mentioning
confidence: 99%
“…Free online mobile phone apps are available to check vision, but most of them have not gained regulatory approval 1718. In a prospective comparative study of app-based home vision testing in children, most families were able to generate results deemed useful for clinical decision making, but parental engagement was low 19…”
Section: What You Should Covermentioning
confidence: 99%
“…The use of home-based screening tools for amblyopia are increasingly advocated as social distancing is practised to minimise the risk of viral transmission. 19 20 Furthermore, COVID-19 related restrictions and lockdowns may have resulted in many children missing out opportunities for amblyopia screening. 19 Home-based screening may offer a solution, 21 but this has not been rigorously assessed and evaluated by systematic review.…”
Section: Introductionmentioning
confidence: 99%
“… 19 20 Furthermore, COVID-19 related restrictions and lockdowns may have resulted in many children missing out opportunities for amblyopia screening. 19 Home-based screening may offer a solution, 21 but this has not been rigorously assessed and evaluated by systematic review. Here, we propose a systematic review to evaluate home-based amblyopia screening tools.…”
Section: Introductionmentioning
confidence: 99%